Precision bacterial immunotherapy: an integrated mechanistic taxonomy and translational roadmap against antimicrobial resistance - Al-Azzani, Hamdi; Arthur Vithran, Djandan Tadum; Aliouat, Hanane; Zhou, Wenhu; Mao, Xiaoqiang (Frontiers in Immunology, 2025)
An integrated, host-directed therapeutic strategy is urgently required to outpace the accelerating threat of antimicrobial resistance (AMR), because pathogen-centred antibiotics are losing efficacy worldwide. The growing threat of antimicrobial resistance has made traditional antibiotics less and less effective, and it has also shown that our pathogen-centered treatment model has systemic flaws. Bacterial immunotherapy offers an alternative that is directed at the host. Still, its many forms, such as innate immune agonists, monoclonal antibodies, engineered cells, CRISPR-based antimicrobials, and aptamer-guided nanoplatforms, have mostly been looked at separately. We put these different approaches together in this narrative review to create a new mechanistic taxonomy that shows how they can be used together to break down biofilms, stop efflux pumps, and get rid of intracellular reservoirs. We then put each modality on a translational continuum, from bench-top proof-of-concept to late-stage trials, and find the most essential delivery, safety, and regulatory problems. Lastly, we describe a precision-first vision that uses multi-omics profiling and theranostic platforms to help with patient stratification, adaptive dosing, and real-time monitoring. This review shows a straightforward way to turn narrative insights into context-sensitive, long-lasting interventions that will work with and maybe even change the future of infectious disease medicine by co-developing immunotherapeutic strategies with advanced diagnostics and stewardship frameworks.